Pemasangan Mirror Safety Dalam Upaya Menekan Angka Kecelakaan Berkendara di RT 002 Kelurahan Karang Rejo - Lina Yuliana; Muhammad Wahid Nugroho (Abdimas Universal, 2024)
The installation of convex mirror aims to reduce the number of accidents in the Gang Rambutan RT 002. This road is the entrance to the main road in Karang Rejo Village, so traffic is heavy every day. Convex mirror are additional road equipment designed to improve visibility for drivers. These convex mirror are usually installed on the side of the road where the driver's view is very limited or obstructed, especially around sharp turns. In this activity, convex mirror were installed in two locations in Karang Rejo RT 002 Village. The location was determined after coordinating with Bhabinkamtibmas, Babinsa, Head of Village Karang Rejo and the Head of RT 002. From this adjustment, it was found that convex mirror was installed in two locations, namely the first point on the main road RT 002 Gang Rambutan and the second point in intersection Gang Rambutan RT 002. After the convex mirror components are installed first, the installation is carried out throughout the day. Therefore, when installing, simply insert it into the hole provided. Based on the results of the review one week after installation, the existence of this convex mirror has benefited the community, increasing the visibility of Gang Rambutan RT 002.